Anti-inflammatory action of geniposide promotes wound healing in diabetic rats - Xiao-yan Chen; Wen-wen Jiang; Yan-ling Liu; Zhao-xia Ma; Jian-qiang Dai (Pharmaceutical Biology, 2022)
Context As a major active iridoid glycoside from Gardenia jasminoides J. Ellis (Rubiaceae), geniposide possesses various pharmacological activities, including anti-platelet aggregation and anti-inflammatory action. Objectives This study explores the effect of geniposide in diabetic wound model by anti-inflammatory action. Materials and methods Diabetic rodent model in Wistar rats was induced by streptozotocin combined with high-fat feed. The selected rats were divided into control group, the diabetic model group and geniposide subgroups (200, 400 and 500 mg/kg), and orally administrated once daily with saline or geniposide. Wound area and histochemical indicators were measured on day 7 after continuous administration, to assess lesion retraction, inflammatory cells and fibroblasts. Results Geniposide notably enhanced lesion retraction by 1.06–1.84 times on day 7 after surgical onset in diabetic rats (p < 0.05). In the pathological experiment by HE staining, geniposide significantly reduced inflammatory cell infiltration and proliferation of fibroblasts in the central lesion regions. In diabetic rats treated with geniposide, the levels of pro-inflammatory factors (tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β)) and IL-6 were significantly reduced (p < 0.05), followed with the increment of IL-10 in a dose-dependent manner. The IC50 of geniposide on TNF-α, IL-1β and IL-6 could be calculated as 1.36, 1.02 and 1.23 g/kg, respectively. It assumed that geniposide-induced IL-10 expression contributed to inhibiting the expression of pro-inflammatory factors. Discussion and conclusions Geniposide promoted diabetic wound healing by anti-inflammation and adjusting blood glucose. Further topical studies are required to evaluate effects on antibacterial activity and skin regeneration.